2019
DOI: 10.1109/access.2019.2913872
|View full text |Cite
|
Sign up to set email alerts
|

Complex Synchronization of a Ring-Structured Network of FitzHugh-Nagumo Neurons With Single-and Dual-State Gap Junctions Under Ionic Gates and External Electrical Disturbance

Abstract: Synchronization plays an essential role in processing information and decisions by neurons and their networks in the brain, and it is useful to study the synchronization of neuron networks, as a part of the process of understanding the functionality of both healthy and diseased brains. In the past, most studies had developed control schemes relating to synchronization problems which were limited to two or three neurons, which cannot depict the dynamic synchronization behavior of neuron networks. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Among those, FHN is the most commonly used model to investigate the synchronization of coupled neurons because of its wide applicability and complex dynamical aspects. In the literature, the subject of neuronal synchronization, using the FHN model, has been intensively examined as a potential application in cognitive engineering 1,20,28,47,57 . Researchers have developed adaptive 20,41 , nonlinear 28 , robust control 23 , neuralnetwork-, fuzzy 74 , and observer-based control schemes 63 to study the synchronization phenomenon in FHN www.nature.com/scientificreports/ neurons under external electrical stimulations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among those, FHN is the most commonly used model to investigate the synchronization of coupled neurons because of its wide applicability and complex dynamical aspects. In the literature, the subject of neuronal synchronization, using the FHN model, has been intensively examined as a potential application in cognitive engineering 1,20,28,47,57 . Researchers have developed adaptive 20,41 , nonlinear 28 , robust control 23 , neuralnetwork-, fuzzy 74 , and observer-based control schemes 63 to study the synchronization phenomenon in FHN www.nature.com/scientificreports/ neurons under external electrical stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…Let us consider a bidirectional ring-structured time-delayed FHN network with different gap junctions and external noise. Mathematically, (1) www.nature.com/scientificreports/ where ϕ 2 (t) is the Gaussian noise 70 source having zero mean and the following correlation function:…”
Section: (B) Network With Noisementioning
confidence: 99%
See 2 more Smart Citations
“…Our approach of combining external feedbacks with neural networks is analogous to a natural phenomenon in biological systems in which networks of neurons interact with each other and are controlled by external feedback loops and other networks 29 . For example recent studies have shown that the challenging task of synchronization between neuron networks can be achieved by feedback controls in the presence of signal delay, noise, and external disturbances 30,31 , and that resonance can be excited and controlled in complex neuron systems by using external feedback signals including chaotic resonances 32,33 . Some initial simplified adaptive ML studies have also begun on coupling the outputs of CNNs to adaptive feedback for real-time accelerator phase space control 34 and for predicting 3D electron density distributions for 3D coherent diffraction imaging 35 .…”
Section: Introductionmentioning
confidence: 99%